PENERAPAN MODEL PEMBELAJARAN CREATIVE PROBLEM SOLVING UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS VIII PADA MATA PELAJARAN SEJARAH KEBUDAYAAN ISLAM DI MTS HUBBUL WATHAN PETAI KECAMATAN SINGINGI HILIR KABUPATEN KUANTAN SINGINGI - Fika Fika; Andrizal Andrizal; Zulhaini Zulhaini (JOM FTK UNIKS (Jurnal Online Mahasiswa FTK UNIKS), 2023)
Based on the results of the study, it was found that in the pre-cycle activities of the learning process in class VIII on the history of Islamic culture at MTs. Hubbul Wathan Petai, Singingi Hilir, Kuantan Singingi district still uses lecture and discussion methods, in this activity the implementation has reached 70% with 1196 learning outcomes an average of 70.35, 10 students who did not complete, 7 students who completed and 41 completeness scores. .18% after that, the first cycle activity was carried out, namely the learning process using creative problem solving learning models, in this activity the application had reached 80% with the number of learning outcomes 1240 an average of 70.59, students who did not complete 5, students who completed 12 and the completeness score is 70.59%. Then continued with the second cycle in this activity the application has reached 90% with the number of learning outcomes 1375 an average of 81, students who did not complete 2, students who completed 15 and the completeness score 88.24%, it can be concluded that the learning outcomes of class students VIII from pre-cycle to cycle I and cycle II has increased.